Effect of storage temperature on the postharvest quality and shelf life of ginger Zingiber officinale rhizome - Shaharudin, Nur Athirah (2015)
Zingiber officinale, commonly known as ginger, is significantly important in the spice trade industry because of its high medicinal importance. Its shelf-life and quality is governed by storage temperature and time. The present study pertains to biochemical changes in ginger rhizome during storage. The objective of this study was to determine the effect of storage temperature on the postharvest quality and shelf life of ginger rhizome. The rhizomes were stored at three different temperature: room temperature (RT) (24 ± 1°C); low temperature (LT) (12 ± 1°C); and chilling temperature (CT) (5 ± 1°C) with three replicates of ± 300 g for each experimental unit. The experimental design was completely randomized design (CRD) with three replicates. The data samples were analyzed at different time intervals: weekly on the first month and every two weeks on the second month and third month, which were analyzed on day 0, 7, 14, 21, 28, 42, 56, 70 and 84. Temperature did affect weight, total soluble solids, pH, acidity and microbial growth of ginger rhizomes when stored at different temperatures. There were significant changes in weight loss, total soluble solids, pH and microbial growth. However, there was no significant changes observed in titratable acidity. Shrivelling and sprouting are the limiting factor for further storage at RT, and the high percentage of water loss was responsible for commercially rejection levels of shrivelling. Rhizomes exhibited chilling injury symptoms as water-soaked lesions with tissue softening, browning, extreme water loss and failure to sprout at the chilling temperature (CT) and rapid deterioration of physical, and physiological properties at RT. Low temperature minimized the biochemical changes and doubled the shelf-life of ginger influenced by temperature and storage time.